Mechanism of leakage of ion-implantation isolated AlGaN/GaN MIS-high electron mobility transistors on Si substrate. (August 2017) - Zhang, Zhili; Song, Liang; Li, Weiyi; Fu, Kai; Yu, Guohao; Zhang, Xiaodong; Fan, Yaming; Deng, Xuguang; Li, Shuiming; Sun, Shichuang; Li, Xiajun; Yuan, Jie; et al.
Abstract: In this paper, we systematically investigated the leakage mechanism of the ion-implantation isolated AlGaN/GaN metal-insulator-semiconductor high electron mobility transistors (MIS-HEMTs) on Si substrate. By means of combined DC tests at different temperatures and electric field dependence, we demonstrated the following original results: (1) It is proved that gate leakage is the main contribution to OFF-state leakage of ion-implantation isolated AlGaN/GaN MIS-HEMTs, and the gate leakage path is a series connection of the gate dielectric Si3 N4 and Si3 N4 -GaN interface. (2) The dominant mechanisms of the leakage current through LPCVD-Si3 N4 gate dielectric and Si3 N4 -GaN interface are identified to be Frenkel–Poole emission and two-dimensional variable range hopping (2D-VRH), respectively. (3) A certain temperature annealing could reduce the density of the interface state that produced by ion implantation, and consequently suppress the interface leakage transport, which results in a decrease in OFF-state leakage current of ion-implantation isolated AlGaN/GaN MIS-HEMTs.